2017
DOI: 10.1111/anae.14180
|View full text |Cite
|
Sign up to set email alerts
|

Peri‐operative management of patients with type‐2 diabetes mellitus undergoing non‐cardiac surgery using liraglutide, glucose–insulin–potassium infusion or intravenous insulin bolus regimens: a randomised controlled trial

Abstract: In this open-label multicentre randomised controlled trial, we investigated three peri-operative treatment strategies to lower glucose and reduce the need for rescue insulin in patients aged 18-75 years with type-2 diabetes mellitus undergoing non-cardiac surgery. Patients were randomly allocated using a web-based randomisation program to premedication with liraglutide (liraglutide group), glucose-insulin-potassium infusion (insulin infusion group) or insulin bolus regimen (insulin bolus group), targeting a gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
39
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 33 publications
3
39
0
1
Order By: Relevance
“…9 A previous trial from our own group in a non-cardiac surgery population showed improved glycaemic control with fewer insulin requirements after preoperative liraglutide administration. 21 Our current data extend these results to patients undergoing cardiac surgery.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…9 A previous trial from our own group in a non-cardiac surgery population showed improved glycaemic control with fewer insulin requirements after preoperative liraglutide administration. 21 Our current data extend these results to patients undergoing cardiac surgery.…”
Section: Discussionsupporting
confidence: 73%
“…To quantify the effect on insulin requirements, we used an insulin bolus algorithm that was proven effective in controlling perioperative BG concentrations. 21 Besides the intervention group in this study, glycaemic control in the placebo group was also quite good, with a mean intraoperative BG of 7.0 mmol/L and only 4% of patients experiencing hyperglycaemia >11.0 mmol/L. It is probable that the glycaemic control in the placebo group was positively influenced by a clinical trial effect, because outside of clinical trials, non-compliance with insulin protocols results in poorer glycaemic control.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…In addition, increasing evidence indicates that incretin therapies have cardiovascular benefits, including reduced inflammation and oxidative stress (30,32) and improved endothelial function (24), which could benefit hospitalized patients with diabetes. Previous studies have reported on the use of native GLP-1 and GLP1-RA infusions in critically ill and surgical patients (33)(34)(35). Besch et al (34) compared the use of intravenous exenatide to insulin infusion in cardiac surgery patients and reported similar glycemic control and reduced insulin use in the ICU with exenatide therapy.…”
Section: Discussionmentioning
confidence: 99%